Analysis of the Impact of Campus Image on Student Loyalty with Student Satisfaction as Intervening Variables - Fakhrudin, Arif (Journal of Economics and Public Health, 2023)
Education is one of the most important parts of life. Currently, education is a basic need that must be met. Because by having quality education, people will have the provisions to compete in the world of work. With awareness of the importance of education, people compete to acquire knowledge, both through formal education and informal education. Consumers will also be very careful in choosing a college so that the time and costs spent are commensurate with what they get from the college's service products. He can usually find out about this from what is promoted by the university in marketing the service products it sells through that institution. Student loyalty can also be created if students feel satisfied with the services provided by the campus. Objective: The aim of this research is to determine the influence of campus image on student loyalty through student satisfaction on the STTKD campus. Method: The type of research used in this research is hypothesis testing. The instrument used in this research is a questionnaire whose validity and reliability have been tested. Then the collected data was analyzed using Structural Equation Modeling (SEM). Results: The research results show that campus image has a significant positive effect on student satisfaction and student loyalty. Then student satisfaction has a significant positive effect on loyalty. Conclusion: Student loyalty at the STTKD campus is positively influenced by campus image and student satisfaction variables.